2007
DOI: 10.1086/508824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Severe Acute Respiratory Syndrome Care on the General Health Status of Healthcare Workers in Taiwan

Abstract: The impact of the SARS outbreak on SARS HCWs was significant in many dimensions of general health. The vitality and mental health status of SARS HCWs 1 month after self-quarantine and off-duty shifts remained inferior to those of the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…12,[15][16][17] Increased workload, fear of infection due to patient care, inadequate training and equipment, and lack of support were risk factors for poor mental and physical health. [18][19][20][21][22] Similar ndings were reported in studies of medical workers who participated in the treatment of MERS patients. [23][24][25] However, we have identi ed no studies that focused on public health workers during outbreak control and prevention, despite their indispensable role in containing the epidemic.…”
Section: Introductionsupporting
confidence: 75%
“…12,[15][16][17] Increased workload, fear of infection due to patient care, inadequate training and equipment, and lack of support were risk factors for poor mental and physical health. [18][19][20][21][22] Similar ndings were reported in studies of medical workers who participated in the treatment of MERS patients. [23][24][25] However, we have identi ed no studies that focused on public health workers during outbreak control and prevention, despite their indispensable role in containing the epidemic.…”
Section: Introductionsupporting
confidence: 75%
“…HCWs who are at the first line of battle under the influence of high fatality and intense media coverage will undoubtedly show the emotion of fear, anxiety, anger and frustration (Lu, Shu, Chang, & Lung, 2004;Maunder, Hunter, Vincent, Bennett, & Mazzulli, 2003). A survey of psychological impacts of 2003 SARS outbreak on HCWs in Taiwai showed that social functioning and immediate mental health were among the worst subscales after caring for patients with SARS (Chen et al, 2007). These results highlighted the emotional and occupational vulnerability of HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…After the SARS epidemic, researchers in Taiwan (Chen et al 2007), Hong Kong (Chua et al 2004), Singapore (Koh et al 2005), and Canada (Maunder 2004, McAlonan et al 2007, Styra et al 2008) all documented significant stress, anxiety, and depression among healthcare workers. However, researchers in Toronto did not find any evidence that the SARS epidemic produced an increase in serious psychiatric disorders (Lancee et al 2008).…”
Section: Psychosocial Needsmentioning
confidence: 99%